2006
DOI: 10.1016/j.neuron.2005.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Imaging Reveals Somatodendritic Chloride Gradient in Retinal ON-Type Bipolar Cells Expressing the Biosensor Clomeleon

Abstract: A somatodendritic gradient of Cl(-) concentration ([Cl(-)](i)) has been postulated to generate GABA-evoked responses of different polarity in retinal bipolar cells, hyperpolarizing in OFF cells with low dendritic [Cl(-)](i), and depolarizing in ON cells with high dendritic [Cl(-)](i). As glutamate released by the photoreceptors depolarizes OFF cells and hyperpolarizes ON cells, the bipolars' antagonistic receptive field (RF) could be computed by simply integrating glutamatergic inputs from the RF center and GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(174 citation statements)
references
References 58 publications
10
162
1
1
Order By: Relevance
“…GABA inputs could evoke a dual-effect in rod-BCs: depolarizing the dendrites and hyperpolarizing the axonal terminals (Duebel et al, 2005;Varela et al, 2005a). Interestingly, we also found that KCC2 was present in PKC-positive rod-bipolar dendrites (see Fig.…”
Section: Nkcc1 In the Outer Retinas In Adult Animalssupporting
confidence: 61%
“…GABA inputs could evoke a dual-effect in rod-BCs: depolarizing the dendrites and hyperpolarizing the axonal terminals (Duebel et al, 2005;Varela et al, 2005a). Interestingly, we also found that KCC2 was present in PKC-positive rod-bipolar dendrites (see Fig.…”
Section: Nkcc1 In the Outer Retinas In Adult Animalssupporting
confidence: 61%
“…Although these mice have previously been used for several purposes (Haverkamp et al, 2005;Duebel et al, 2006;Pond et al, 2006), this paper provides the first comprehensive description of these mice and the properties of the transgenically expressed Clomeleon. We also demonstrate that dynamic changes in [Cl − ] i resulting from synaptic activity can be detected in these mice, establishing a new avenue for imaging mechanisms of synaptic inhibition and inhibitory network activity.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike organic Cl − dyes (Verkman, 1990), Clomeleon expression can be targeted to distinct populations of neurons. These properties make Clomeleon suitable for studying many poorly understood aspects of [Cl − ] i regulation, including activity-dependent ionic plasticity (Kaila, 1994;Payne et al, 2003), compartmental gradients of [Cl − ] i (Duebel et al, 2006;Szabadics et al, 2006), sensory signal transduction (Reuter et al, 1998), and pathophysiological mechanisms in a multitude of diseases (Payne et al, 2003;Pond et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Photoreceptors in the surround of the ganglion cell's receptive field may depolarize horizontal cells (Fig. 8Bii), which excite ON bipolar cells (Duebel et al 2006) and finally the ON ganglion cell. This multisynaptic retinal circuitry leads to long-latency spikes (Figs.…”
Section: Characterization Of Capacitive Stimulation Arraymentioning
confidence: 99%